EFL TEACHER EDUCATOR’S STRATEGIES IN DEVELOPING TEACHING MATERIALS FOR ONLINE SPEAKING CLASSES USING GOOGLE CLASSROOM - Aris Munandar (Universitas Galuh, 2022)
The objective of this study was aimed 1) to figure out how EFL teacher educator develops teaching materials for speaking lessons in online classes using Google Classroom; 2) to find out the obstacles EFL teacher educator in developing teaching materials for speaking lessons in online classes using Google Classroom; 3) and to find out student perceptions of EFL teacher educator in developing teaching materials for the online speaking class using Google Classroom. The present study used a qualitative Case study design. Seven students from the 1D English education program and an English lecturer took part in this research. The data were gained through interview and questionnaire. To analyse the interview, the researcher first transcribed and then made interpretation from it. The questionnaire data were analysed using Likert Scale measurement. The findings revealed that the lecturer has considerations and steps to developing teaching materials. In addition, based on the findings, the researcher analysed that the teaching materials made by lecturers can be understood well by students and online speaking learning using Google Classroom can be done well. The researcher suggests for lecturers to make more variations in developing teaching materials so that class learning can be more fun and easy to understand, and help students to keep their interest and motivation in the learning activity.